Fractional Integral Inequalities via Atangana-Baleanu Operators for Convex and Concave Functions - Ahmet Ocak Akdemir; Ali Karaoğlan; Maria Alessandra Ragusa; Erhan Set (Journal of Function Spaces)
Recently, many fractional integral operators were introduced by different mathematicians. One of these fractional operators, Atangana-Baleanu fractional integral operator, was defined by Atangana and Baleanu (Atangana and Baleanu, 2016). In this study, firstly, a new identity by using Atangana-Baleanu fractional integral operators is proved. Then, new fractional integral inequalities have been obtained for convex and concave functions with the help of this identity and some certain integral inequalities.